Use of Evidence-Informed Deliberative Processes - Learning by Doing; Comment on "Use of Evidence-informed Deliberative Processes by Health Technology Assessment Agencies Around the Globe" - Anthony J. Culyer (Kerman University of Medical Sciences, 2020)
The article by Oortwijn, Jansen, and Baltussen (OJB) is much more important than it appears because, in the absence of any good general theory of "evidence-informed deliberative processes" (EDP) and limited evidence of how they might be shaped and work in institutionalising health technology assessment (HTA), the best approach seems to be to accumulate the experience of a variety of countries, preferably systematically, from which some general principles might subsequently be inferred. This comment reinforces their arguments and provides a further example.